2021
DOI: 10.2174/1567205018666210628100812
|View full text |Cite
|
Sign up to set email alerts
|

High Fat Diet Aggravates AD-Related Pathogenic Processes in APP/PS1 Mice

Abstract: Background: Alzheimer’s disease (AD) is the most common neurodegenerative disorder and negative life-style factors may contribute to its etiopathogenesis. Substantial evidence from humans and murine models reveal that Insulin Resistance (IR) associated with high fat diet (HFD) increase the risk of developing AD and age-related amyloidogenesis. Objective: To corroborate and clarify the influence of HFD on amyloidogenesis and cognitive deficits in AD model mice. Results: We here show that a four months HFD-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 67 publications
0
3
0
Order By: Relevance
“…Walker et al reported ten-month HFD treatment increased the level of tau phosphorylation in the hippocampus of AD model mice [ 40 ]. Gong et al also found that four-month HFD feeding for AD model mice increased insulin resistance and β-amyloid accumulation which is another pathological hallmark of AD [ 41 ]. Accumulating studies indicate that obese elderly people exhibit an increase in tau phosphorylation of the hippocampus.…”
Section: Discussionmentioning
confidence: 99%
“…Walker et al reported ten-month HFD treatment increased the level of tau phosphorylation in the hippocampus of AD model mice [ 40 ]. Gong et al also found that four-month HFD feeding for AD model mice increased insulin resistance and β-amyloid accumulation which is another pathological hallmark of AD [ 41 ]. Accumulating studies indicate that obese elderly people exhibit an increase in tau phosphorylation of the hippocampus.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, obesity or hyperglycaemia can cause up-regulation of hepatic expression of the immature form of Bace1 that is implicated in insulin receptor shedding ( 36 ). Furthermore, long-term exposure to high-fat diet increases Bace1 expression in the brain promoting β-amyloid (Aβ) accumulation and cognitive deficits ( 37 ), while treatment with Bace1 inhibitor reduces circulating levels of Aβ 1-42 peptide ( 38 ) in high-fat diet-induced obese mice. In the brain, Bace1 is expressed in the cortex, hippocampus ( 39 ) and the hypothalamus including ARH ( 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…[1] AD is highly heterogeneous, which is related to multitude of genetic and environmental factors. [2,3] While advanced age (beyond 65 years) and genetic predisposition (APOE 𝜖4 allele) are the principal risk factors for AD, a variety of etiological factors, such as obesity, diabetes, and long-term consumption of high-fat diet (HFD), [4][5][6] have also been postulated to contribute to cognitive deficits and escalate AD susceptibility. [7] Epidemiological research has indicated that consuming a significant amount of saturated fat for a duration of 4-6 years (particularly during middle age) poses a substantial threat in terms of the likelihood of developing mild cognitive impairment and dementia in individuals aged 65 and above, a jeopardy that is further compounded in the presence of the APOE 𝜖4 allele.…”
Section: Introductionmentioning
confidence: 99%